2020
DOI: 10.1016/j.jcmgh.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-CoA Carboxylase Inhibition Improves Multiple Dimensions of NASH Pathogenesis in Model Systems

Abstract: The pathogenesis of nonalcoholic steatohepatitis is multifactorial, involving steatosis, lipotoxicity, hepatic inflammation, and fibrosis. The present studies show that acetyl-CoA carboxylase inhibition produces direct improvements in hepatic steatosis, inflammation, and fibrosis in both primary human cell systems and rodent nonalcoholic fatty liver disease/nonalcoholic steatohepatitis models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 37 publications
4
54
0
Order By: Relevance
“…In line with previous observations made through use of other ACC inhibitors, 4 , 5 PF-05221304 diminished de novo lipogenesis, both in isolated primary human cells and in Western diet–fed rats. 6 However, in contrast with previous studies that had reported an elevation in circulating triglyceride levels, 4 , 5 no significant changes in body weight, fasting glucose, triglyceride, and cholesterol levels were observed. Interestingly, although dose-dependent reductions in hepatic triglyceride levels were identified in the PF-05221304-treated Western diet model, no effects on the extent of hepatic steatosis were observed when administrating the drug to diethylnitrosamine (DEN) and choline deficient and high-fat diet (CDAHFD) rat models.…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…In line with previous observations made through use of other ACC inhibitors, 4 , 5 PF-05221304 diminished de novo lipogenesis, both in isolated primary human cells and in Western diet–fed rats. 6 However, in contrast with previous studies that had reported an elevation in circulating triglyceride levels, 4 , 5 no significant changes in body weight, fasting glucose, triglyceride, and cholesterol levels were observed. Interestingly, although dose-dependent reductions in hepatic triglyceride levels were identified in the PF-05221304-treated Western diet model, no effects on the extent of hepatic steatosis were observed when administrating the drug to diethylnitrosamine (DEN) and choline deficient and high-fat diet (CDAHFD) rat models.…”
mentioning
confidence: 61%
“…Interestingly, although dose-dependent reductions in hepatic triglyceride levels were identified in the PF-05221304-treated Western diet model, no effects on the extent of hepatic steatosis were observed when administrating the drug to diethylnitrosamine (DEN) and choline deficient and high-fat diet (CDAHFD) rat models. 6 Because of the known association of increasing levels of infiltrating inflammatory cells during the NASH pathology, and the recent association of an elevated ratio of Th17-inflammatory over Treg-cells to NASH progression, 7 Ross et al 6 decided to also investigate the effect of PF-05221304 on the inflammatory outcome. Interestingly, they found that the drug suppresses the polarization of T cells toward the proinflammatory Th17 T cells, but not the anti-inflammatory Treg cells.…”
mentioning
confidence: 99%
See 3 more Smart Citations